Integrative transcriptomics and metabolomics reveal neuroendocrine-lipid crosstalk and adenosine signaling in broiler under heat stress - Bingxing An; Peihao Liu; Zhirui Yang; Fan Ying; Dawei Liu; Jie Wen; Guiping Zhao (BMC Genomics)
Abstract Background Heat stress (HS) is a significant challenge in poultry, negatively impacting feed efficiency and survival. These adaptive responses could lead to disrupted lipid metabolism, impaired immunity, and neural damage. We hypothesized that the neuroendocrine system plays a central role in HS responses by activating the hypothalamic-pituitary-adrenal and sympathetic-adrenal-medullary axes. This study explores the neural transcriptomic changes and metabolomic profile subjected to HS, aiming to unravel the complexity of nervous adaptive responses, including the disrupted lipid metabolism, impaired immunity, and neural damage processes. Results Based on the designed chicken HS model, we identified 1,871 serum metabolites, with 149 differentially accumulated metabolites (DAMs), including ursodeoxycholic acid, niacinamide, and prostaglandin E1. These metabolites indicated disrupted lipid homeostasis and potential adaptive mechanisms to mitigate stress. Key metabolite biomarkers were identified using random forest, including 2-(Methylthio)phenol, and Deca-2,4,6-triynedioic acid, enriched in immune and stress-related pathways such as glutathione metabolism and nicotinamide metabolism. Then, the comparative transcriptome analysis of the hypothalamus and pituitary revealed 358 differentially expressed genes (DEGs), highlighting tissue-specific adaptive pattern. The hypothalamus DEGs enriched in neurotransmitter biosynthesis and Notch signaling pathways, while the pituitary DEGs exhibited changes in calcium and insulin signaling pathways. Finally, by integrating omics data with machine learning, we uncovered key stress-relief mechanisms involving adenosine accumulation and adrenaline signaling. Adenosine signaling emerged as a critical pathway for thermoregulation through vascular relaxation, while adrenaline signaling regulated calcium homeostasis and muscle contraction under stress. Conclusions This study provides comprehensive insights into the molecular adaptations of HS in broiler, emphasizing the roles of lipid metabolism, neuroendocrine regulation, and vascular dynamics. The findings highlight the potential of integrating transcriptomics and metabolomics with machine learning to identify biomarkers and pathways involved in HS adaptation. These results could provide an effective theoretical basis of the preventive and treatment measures for HS.